2015
DOI: 10.1007/s13365-015-0334-2
|View full text |Cite
|
Sign up to set email alerts
|

Quinolinic acid/tryptophan ratios predict neurological disease in SIV-infected macaques and remain elevated in the brain under cART

Abstract: Activation of the kynurenine pathway (KP) of tryptophan catabolism likely contributes to HIV-associated neurological disorders. However, KP activation in brain tissue during HIV infection has been understudied, and the effect of combination anti-retroviral therapy (cART) on KP induction in the brain is unknown. To examine these questions, tryptophan, kynurenine, 3-hydroxykynurenine, quinolinic acid, and serotonin levels were measured longitudinally during SIV infection in striatum and CSF from untreated and cA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…Concordant with our previous data in brain tissue (32), we found that upstream enzymes in the KP ( IDO1, KMO , and KYNU ) displayed more upregulation during acute infection than downstream enzymes ( HAAO and QPRT ). Intriguingly, we also found that IDO1 expression in the spleen actually peaked prior to peak spleen viral loads (days 4 vs. 7 p.i.)…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Concordant with our previous data in brain tissue (32), we found that upstream enzymes in the KP ( IDO1, KMO , and KYNU ) displayed more upregulation during acute infection than downstream enzymes ( HAAO and QPRT ). Intriguingly, we also found that IDO1 expression in the spleen actually peaked prior to peak spleen viral loads (days 4 vs. 7 p.i.)…”
Section: Discussionsupporting
confidence: 92%
“…We thus analyzed the expression of IDO1 mRNA as well as other key enzymes in the KP in spleens of the SIV-infected macaques by NanoString. Paralleling trends in the CNS of these animals (32), we found that upstream enzymes ( IDO1, KMO , and KYNU ) displayed significant mRNA upregulation during at least one phase of infection (Figures 5A–C), while downstream enzymes ( HAAO and QPRT ) were either downregulated or unchanged (Figures 5D,E). Importantly, IDO1 was significantly elevated only during acute infection (Figure 5A, p  = 0.012 at day 4 p.i.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…The depletion of tryptophan at the site of infection can be a protective immune mechanism for microorganisms, however prolonged depletion of tryptophan can lead to immunosuppression by T cell exhaustion. The quinolinic acid/tryptophan ratio was reported to be a biomarker of neurological disease in SIV-infected macaques (Drewes et al, 2015). In HIV-1 infected individuals, cART was shown to normalize the tryptophan metabolism (Jenabian et al, 2015).…”
Section: Discussionmentioning
confidence: 99%